1996
DOI: 10.2307/2269493
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Dwarf Mistletoe on Bird Communities in Colorado Ponderosa Pine Forests

Abstract: Dwarf mistletoes (Arceuthobium spp.) are parasitic plants that are widely distributed in coniferous forests of the northern hemisphere. Because the effects of dwarf mistletoes on their host trees include stunted growth, reduced seed production, and death, these mistletoes may have a substantial influence on forest structure. Studies of the effects of dwarf mistletoe on forest communities have focused primarily on their influence on timber production. We studied the effects of southwestern ponderosa pine dwarf … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 33 publications
6
60
0
Order By: Relevance
“…Importantly, the patterns of presence of fruit did not coincide across our survey sites (maximum 100 km apart), and yet the presence of bird species was associated with site-specific timing of the presence of fruit. Therefore, although we are not able to discount entirely ecosystem-wide effects such as the detectability of birds (Field et al 2002), spring and winter migration (see review on partial migration by Chan 2001) and surges driven by rainfall that attract locally mobile species (as well as promoting recruitment and fruiting of mistletoes ;Reid 1987;Yan and Reid 1995), the findings of the present study are consistent with those of previous studies that have observed a positive link between increased species richness and density of mistletoes (Turner 1991;Bennetts et al 1996), and manipulative studies comparing the avifauna of two adjacent woodland remnants, one of which had been manually cleared of mistletoe (Watson 2002;Watson and Herring 2012). Reid (1986) reported that mistletoe is one of the few reliable sources of fruit in eucalypt forests of south-eastern Australia, and although we only recorded fruiting phenology over 1 year, anecdotal observations (K. Napier, pers.…”
Section: Reliability Of Mistletoe Resourcessupporting
confidence: 89%
See 1 more Smart Citation
“…Importantly, the patterns of presence of fruit did not coincide across our survey sites (maximum 100 km apart), and yet the presence of bird species was associated with site-specific timing of the presence of fruit. Therefore, although we are not able to discount entirely ecosystem-wide effects such as the detectability of birds (Field et al 2002), spring and winter migration (see review on partial migration by Chan 2001) and surges driven by rainfall that attract locally mobile species (as well as promoting recruitment and fruiting of mistletoes ;Reid 1987;Yan and Reid 1995), the findings of the present study are consistent with those of previous studies that have observed a positive link between increased species richness and density of mistletoes (Turner 1991;Bennetts et al 1996), and manipulative studies comparing the avifauna of two adjacent woodland remnants, one of which had been manually cleared of mistletoe (Watson 2002;Watson and Herring 2012). Reid (1986) reported that mistletoe is one of the few reliable sources of fruit in eucalypt forests of south-eastern Australia, and although we only recorded fruiting phenology over 1 year, anecdotal observations (K. Napier, pers.…”
Section: Reliability Of Mistletoe Resourcessupporting
confidence: 89%
“…Although the influence of these resources on the structure of an avian community can be difficult to elucidate ), several studies have described the link between the presence of aerial mistletoes and greater avian species richness (e.g. Turner 1991;Bennetts et al 1996;Watson 2002;Watson and Herring 2012). The present study clearly indicates a correlation between the presence of bird species and the temporal availability of ripe mistletoe fruit.…”
Section: Degree Of Consumer Specificitysupporting
confidence: 60%
“…One study in Colorado suggested that ponderosa pine forests with dwarf mistletoe have a greater diversity of bird species as well as higher populations of elk and deer than healthy pine stands (22). However, a similar study conducted in northern Arizona reported a positive correlation for only some birds, primarily secondary cavity nesting species, in ponderosa pine forests with dwarf mistletoe (161).…”
Section: Mistletoes Influence On Wildlife Habitatmentioning
confidence: 99%
“…The management of mistletoes to benefit wildlife is in the early stages of development, but because the positive relationship is so clear, wildlife biologists and ecologists are recommending that mistletoes be ecologically managed rather than eradicated (22,43,158,219). Although the relationship between wildlife and mistletoes is well known, published records of mistletoe management for wildlife are scarce.…”
Section: Managing Mistletoesmentioning
confidence: 99%
“…Mistletoes provide food, foraging sites, and nesting for numerous species; structural changes from brooms, snags, and openings (Parmeter 1978, Tinnin 1984 benefit the abundance and richness of nesting passerine birds (Bennetts et al 1996).…”
Section: Dwarf Mistletoesmentioning
confidence: 99%